71.3: Quantification of Water Penetration and Degradation through Adhesives Applicable to Flexible OLED Design. Issue 1 (June 2015) - Ohzu, Yoshiko; Takahagi, Hisashi; Uehigashi, Atsushi; Kubota, Hirofumi; Sugimoto, Akira; Ohata, Hiroshi; Suzuki, Akira; Hara, Shigeki; Tanamura, Mitsuru; Minakata, Takashi; Kimura, Masayuki; Ibaraki, Nobuki; et al.
Abstract : A reliable evaluation method applicable to flexible OLEDs is developed to quantify water penetration from an adhesive edge face. The adhesive's apparent water diffusion coefficient obtained by this method provides the water penetration time and elucidates the pathway. Moreover, the proposed method can predict the start time of degradation.